Design and development of innovator self-assessment questionnaire for students in grade 6: Utilizing educational design research - Mirattanaphrai, Pantechat; Srikoon, Sanit (Social sciences & humanities open, 2025)
Fostering innovation in Grade 6 students cultivates future skills for future success. Current tools need a comprehensive assessment of innovators in Grade 6 students. This study aims to (1) analyze and explore perspectives for designing the Innovator Self-Assessment Questionnaire for Grade 6 Students (ISQ6), (2) develop the ISQ6, and (3) evaluate and reflect on its effectiveness. Grounded in educational design research, this study highlights the need to assess innovation in Grade 6 students as school policies increasingly emphasize innovation development. The ISQ6 was developed through a collaborative effort involving multiple stakeholders and comprises 24 items aligned with theories of innovation and psychology relevant to Grade 6 students. The questionnaire significantly enhances ISQ6 scores across five key factors: connective thinking skills, observable skills, networking skills, curiosity and imagination, and creativity and divergent thinking. Validation of the ISQ6 was achieved using second-order confirmatory factor analysis, with all goodness-of-fit indices meeting accepted standards and strong Cronbach's alpha coefficients. Furthermore, the new design theory suggests that the ISQ6 possesses a robust structure and can adapt the phrasing of items to suit various educational levels. •Developed Innovator Self-Assessment Questionnaire for Students in Grade 6 (ISQ6).•Implementing educational research design (EDR) to design and develop ISQ6.•Adapt the construction of van den Akker's (1999) design principal approach to McKenney and Reeves's (2019) EDR as a more challenging theory construction in EDR.•Focus on advancing ISQ6 development methodology through the theory adaptation of EDR in students in grade 6.•Provided new theory construction into ISQ6's application in innovator classroom challenges.